Redução fotocatalítica de nitrato e nitrito usando o semicondutor sulfeto de zinco - Sousa, Ronaldo Teixeira (2024)
Nitrate and nitrite contamination rates in water courses increased after the implementation of the Haber-Bosch process in the first decade of the 20th century. The most commonly used methods for nitrite removal consist of phase separation treatments, which can result in the accumulation of brines and sludge. In this scenario, heterogeneous photocatalysis emerges as a promising process for the photoreduction of nitrate and nitrite in an aqueous medium, since its application generates little residue after the reaction process. Additionally, the low energy cost and the possibility of reusing the catalyst are important factors for application. Different semiconductor materials can be used as a photocatalyst, however, zinc sulfide (ZnS) stands out due to its conduction band potential, which is -1.9 eV (vs NHE at pH 7.0), which makes it a excellent candidate for reduction reactions. To reduce the recombination rate of charges formed during the photoactivation of the catalyst, low levels of silver (≤ 1.0%) were added to the ZnS surface using the wet impregnation method. Therefore, synthesizing, characterizing and evaluating the photocatalytic performance of pure and silver-impregnated ZnS against nitrate reduction in aqueous media constitute the objective of the work. The synthesis of the catalyst was carried out by the hydrothermal method, using two sources of Zn (zinc acetate and zinc nitrate) with thiourea in a molar ratio of 1:3. To characterize the material, X-ray diffraction (XRD), X-ray fluorescence (XRF) and diffuse reflectance spectroscopy (DRS) analyzes were carried out to better understand the structural and optical properties of the catalyst. The ZnS samples presented diffraction peaks with different widths, resulting in different average crystallite size and microstrain. The chemical composition of ZnS is mainly composed of zinc (Zn) and sulfur (S), with a small amount of tungsten (W), as evidenced by XRF data. The band gap determined via ERD was 3.2 and 3.6 eV, respectively, for samples prepared by zinc nitrate and zinc acetate. However, the addition of Ag does not affect the band gap value. For the photocatalytic tests, the incidence of 8.01020 photons in the solution led to a conversion of 20.8 and 33.4% of nitrate for the experiments carried out in the presence of formic acid and under bubbling of , respectively. Nitrite photoreduction achieved maximum conversion, 100%, with a relative yield of 97% to N2 in 3 h of reaction.